Collaborating to improve child and youth mental health in Nunavik - Fraser, Sarah; Rouillard, Rémy; Nadeau, Lucie; D’Ostie Racine, Léna; Mickpegak, Raymond (Études/Inuit/Studies)

(untitled) (Association Inuksiutiit Katimajiit Inc., 2016)
Following various reports highlighting the lack of mental health services for children and youth in Nunavik (Quebec, Canada), high rates of child placements under youth protection, and gaps in the coordination of services, the Regional Partnership Committee of Nunavik decided to prioritize collaborative, community-based approaches to the health and wellbeing of children, youth, and their families. It is in this context that the regional project Ilagiinut (‘For families’) was initiated and is being piloted in Kuujjuaraapik. In mental health care, collaborative practices are highly valued, and various models are flourishing. However, collaborative care models are not necessarily easy to implement and involve a variety of ingredients, including trust, strong partnerships, clarity of roles, and power dynamics, all of which are influenced by culture and context. In this study, we conducted a total of 54 interviews with administrators, clinicians, and Inuit family members to explore their everyday expectations for and experiences with child and youth mental health services and collaboration between people involved in care. In our analysis we explore how context influences expectations, beliefs, and experiences, and ultimately how these factors impact the nature of services offered to children, youth, and families. The aim is to shed light on obstacles to and facilitators of collaboration in child and youth mental health in order to inform individuals, communities, and organizations that are trying to change policy and practice.